Predictive Factors of Academic Procrastination: A Cross-Cultural Comparison between Indonesian and Egyptian Students - Syafii, Muhammad Hisyam; Purnomo, Halim; Ramadhan, Cahyo Setiadi; Azhari, Husain (Psikis : Jurnal Psikologi Islami, 2024)
This study explored the predictive factors of academic procrastination through a comparative cross-sectional analysis between Indonesian and Egyptian students. Academic procrastination is a widespread issue with negative implications on students' academic performance and psychological well-being. This research examined the role of personality traits such as maladaptive perfectionism, self-efficacy, self-regulation, and time orientation in predicting procrastination behaviour. The study involved 50 undergraduate students (25 from each country), selected through stratified random sampling. Data were collected via validated instruments including the Pure Procrastination Scale, Academic Self-Efficacy Scale, and Zimbardo Time Perspective Inventory. The results revealed that Indonesian students had a higher average academic procrastination score (M = 45.60, SD = 7.12) compared to Egyptian students (M = 43.20, SD = 6.89), though the difference was not statistically significant (p > 0.05). Both groups demonstrated similar levels of self-efficacy (M = 34.50 for Indonesia, M = 34.20 for Egypt). Maladaptive perfectionism was more prevalent in Indonesian students (M = 42.20, SD = 5.85) compared to their Egyptian counterparts (M = 39.80, SD = 6.12). Egyptian students, however, showed better self-regulation (M = 73.90, SD = 7.50) compared to Indonesian students (M = 70.50, SD = 8.30). Furthermore, Egyptian students were more future-oriented (M = 58.40, SD = 6.85), while Indonesian students were more present-oriented (M = 55.40, SD = 6.95). The findings highlighted the influence of cultural factors on procrastination, with future-oriented time perspectives in Egyptian students linked to better self-management. These results suggested that culturally sensitive interventions focusing on enhancing self-regulation and addressing maladaptive perfectionism could mitigate academic procrastination